Optimalisasi supply chain management produk olahan ikan hasil tangkap di era Industri 4.0 - Achmad Misbah; Hikmatul Faizah Muyasaroh (Fakultas Pertanian Universitas Yudharta Pasuruan, 2019)
The UMKM which is the target of this research is the UMKM which is engaged in processing fish caught in Pasuruan Regency. There are several superior products of processed fish caught in Pasuruan Regency which are managed by UMKM so far so many and can be one alternative to improve the welfare of MSME entrepreneurs. However, from the processed fishery products to become a valuable product, a good management is needed so that the supply or availability of catched fish is sufficient in order to equalize and fulfill the desired demand. In supporting this inventory control activity, a management concept is needed that can regulate the flow of goods and information that is precise and accurate from the supply chain, namely the concept of Supply Chain Management (SCM). The focus of the research is on how to manage the supply chain of fish raw materials from captured products through research methods using Supply chain Management (SCM) with the Fuzzy Analytical Hierarchy Process (AHP) method, to then proceed with the implementation of a sales development strategy for MSME Coastal Superior Products. From the results of the analysis and discussion obtained in the determination of supplier selection criteria, a pairwise comparison between criteria, sub-criteria and alternatives using the Fuzzy AHP method to produce weights. Based on the criteria and sub-criteria in supplier selection, overall supplier A (UMKM in the Lekok District Region) was rated as the best supplier weighing 1,699, the second priority was supplier B (UMKM in the Nguling District Region) with a weight of 1,345, while supplier C (UMKM in the Region Kraton District) is the last priority with a weight of 1,098